Electrochemical performance of Fe-doped SnSe material electrodes for supercapacitors - Dar M.A.; Majid S.R.; Satgunam M.; Batoo K.M.; Kalpana S.; Arularasan P.; Fareed S.S.; Moholkar A.V.; Shembade U.V. (Elsevier Ltd, 2025)
This paper synthesized Fe-doped SnSe nanoparticles (NPs) through the co-precipitation technique. The X-ray diffraction (XRD) confirms the orthorhombic crystal structure of Fe-doped SnSe NPs. The chemical states of Sn, Fe and Se elements were identified by X-ray photoelectron spectroscopy (XPS) and energy dispersive X-ray spectroscopy (EDAX). The galvanostatic charge-discharge (GCD) was used to measure the power efficiency of Fe-doped SnSe electrodes. The specific capacitance of 1283 F/g at a current density of 5 A/g was obtained using a three-electrode system. Further, the Fe-doped SnSe electrode shows a specific energy (Es) of 64 Whkg?1 at a specific power (Ps) of 1500 Wkg?1, respectively. The Fe-doped SnSe electrode exhibits a capacitance retention of 101 % for 1000 GCD cycles in a two-electrode system. This study confirms that the Fe-doped SnSe electrodes are the substitute and life-lasting electrodes for supercapacitor devices. ? 2024